(3GdCSS , GdfXQjGJ , GdJWHjbGJ GdYedjIs - (3fGFd YHO GdMGaX(B, (3GdYhGedIs ((3YeGf(B:s (3OGQ RgQGf(B,s, 2010)
(3eaghe GOQGI GdJfejI , fXQjGJ GdJfejI h GdJfejI GdGOGQjI , GdJNWjW GdJfehj h GdGWGQ GdeDSSj h GdJfXjej ddJfejI , Jehjd GdJfejI , GdJfejI GdeMdjI h GdJfejI aj GdGSdGe h CNjQG bVGjG JfehjI eJNUUIs
(3edMb U(B.189 (3; eQGLY U(B.203s
Keywords: (3GdJNWjW GdJfehjs; (3GdJfejIs; (3GdJfejI GdEOGQjIs